(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
children’s surgery center under Samarkand State Medical University in 1996-2022, 63 children were diagnosed with various types of chest injuries and localization. 39 patients with mixed chest injuries. 8 patients received toracotomy , 22 patients received videotorocoscopic operative intervention. The age of patients was 3 – 15. 39 patients who had been treated with mixed chest injuries were put through a retrospective examination. The patients were divided into 4 guruchs under the Algover classification of shock holiness. Surgical access was carried out on the basis of the patient’s weight level and the sagging of the Algover shock index, and its treatment by VTS was objectively predicted. The post-thoracic injury survival in Bol was achieved by correlating the level of shock on the Vvtriss scale and injuries in the patient.